IN BETWEEN SUPERPOWERS: LIMINALITY AND WESTERNIZATION IN WEI HUI’S SHANGHAI BABY (1999) - Sakinah, Mutiara; Adipurwawidjana, Ari J; Prabasmoro, Tisna (Lire Journal (Journal of Linguistics and Literature), 2024)
Shanghai Baby (1999), a novel by Wei Hui, tells the story of a Shanghai woman named Coco who is caught between two superpowers, China and the West, personified by the characters Tian Tian, a native Chinese man with no passion for life, and Mark, a white German man who is dominant in every way. This study aims to identify the tension experienced by both Coco and the novel Shanghai Baby in such a liminal position through narrative content and reactions in the surrounding political economy and cultural discourse. Through a close reading of the text within the theoretical framework of Bhabha's (1994) concept of in-betweenness and third space, we argue that the liminality displayed within the text and based on the novel's highly Westernized narrative structure creates a liminal state for the novel. As such, while the narrative is set in China and was originally written in Chinese, the novel represents Western ideological imagination, underscored by its economic success in its translated form in English.